DO FEMALE GENERATION Z HAVE PURCHASE INTENTION ON GREEN COSMETIC BASED ON THEIR ENVIRONMENTAL KNOWLEDGE, ENVIRONMENTAL CONCERN, HEALTH CONSCIOUSNESS, ATTITUDE AND SUBJECTIVE NORM? - Lius, Silvianie; Salim, Lina (STIE Pelita Nusantara Semarang, 2024)
This study aims to explore the influence of environmental knowledge, environmental concern, and health awareness on the purchase intention of green cosmetics with the mediation of subjective norms and attitudes towards green cosmetics. The object of this study is green cosmetics and 400 female respondents aged 18-23 years in the area of Jabodetabek with a non-probability method of purposive sampling technique. Empirical data processing using partial least square (PLS) software. Nine hypotheses were proposed and all hypotheses were well accepted. The results prove that environmental knowledge, environmental concern, and health awareness have a positive and significant influence on the purchase intention of green cosmetics. Subjective norms and attitudes towards green cosmetics mediate between the independent variables and green cosmetics purchase intention. Improving environmental knowledge, environmental concern, and health awareness is the key to increasing the purchase intention of green cosmetics among consumers.